(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2023)
In philosophy, the term “religious language” aims to provide an explanation of the meaning of religious sentences and expressions. In the Malay intellectual tradition, religious language is commonly referred to as language in Islamic texts, which are studied under the umbrella of Islamic studies, such as tafsir al-Quran, ilmu kalam or monotheism, usul fiqh and mysticism. However, the importance of religious language in Malay philosophy seems to be neglected, both in philosophy of religion and philosophy of language. This article discusses (1) the factors of the neglect of religious language in Malay philosophy and (2) the enhancement of the significance of religious language in contemporary Malay philosophy. The data of this discussion are four issues of religious language that arose as a result of the philosophical attempts of some Malay Muslim thinkers to explain the meaning of religious sentences and expressions. There are factors that contribute to the neglect of religious language in Malay philosophy, such as Malay pessimism towards philosophy and legal provisions that preserve religious language from philosophical arguments. The significance of religious language as a branch of religious philosophy in contemporary Malay philosophy could be enhanced, not only by harmonising the significance of philosophy in religion and language, but also correcting misunderstanding about philosophy, including strengthening the existing philosophy subject as a core subject in tertiary education level. Dalam falsafah, istilah “bahasa agama” bertujuan memberikan penjelasan tentang makna ayat dan ungkapan agama. Dalam tradisi intelektual Melayu, bahasa agama lazimnya dirujuk sebagai bahasa dalam teks-teks Islam, yang dikaji di bawah payung pengajian Islam, seperti tafsir al-Quran, ilmu kalam atau ilmu tauhid, usul fikah dan tasawuf. Namun begitu, kepentingan bahasa agama dalam falsafah Melayu seolah-olah diabaikan, baik dalam falsafah agama mahupun falsafah bahasa. Makalah ini membincangkan faktor pengabaian bahasa agama dalam falsafah Melayu dan peningkatan kepentingan bahasa agama dalam falsafah Melayu kontemporari. Data perbincangan ini ialah empat isu bahasa agama yang tercetus ekoran usaha kefalsafahan beberapa pemikir Muslim Melayu untuk menjelaskan makna ayat dan ungkapan agama. Terdapat faktor yang menyumbang kepada pengabaian bahasa agama dalam falsafah Melayu, seperti pesimisme Melayu terhadap falsafah dan peruntukan undang-undang yang memelihara bahasa agama daripada penghujahan falsafah. Kepentingan bahasa agama sebagai cabang falsafah agama dalam falsafah Melayu kontemporari dapat ditingkatkan, bukan hanya dengan mengharmonikan kepentingan falsafah dalam agama dan bahasa, tetapi juga memperbetulkan salah faham tentang falsafah, termasuk memperkasa kursus falsafah sedia ada sebagai kursus teras pada peringkat pengajian tinggi.